2021
DOI: 10.1186/s13195-020-00761-9
|View full text |Cite
|
Sign up to set email alerts
|

Metformin attenuates plaque-associated tau pathology and reduces amyloid-β burden in APP/PS1 mice

Abstract: Background The neuropathological hallmarks of Alzheimer’s disease (AD) are amyloid-β (Aβ) plaques and neurofibrillary tangles (NFTs). The amyloid cascade theory is the leading hypothesis of AD pathology. Aβ deposition precedes the aggregation of tau pathology and Aβ pathology precipitates tau pathology. Evidence also indicates the reciprocal interactions between amyloid and tau pathology. However, the detailed relationship between amyloid and tau pathology in AD remains elusive. Metformin might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 63 publications
5
47
0
Order By: Relevance
“…Metformin protected rats against from methamphetamine-induced neurodegeneration via the modulation of Akt/GSK3 or CREB/BDNF signaling pathway, and the amelioration of behavioral changes such as anxiety, depression and cognitive deficits( Keshavarzi et al, 2019 ). Metformin attenuated spatial memory deficits, neuron loss in the hippocampus, decreased Aβ plaque load and chronic inflammation in the hippocampus and cortex, and enhanced neurogenesis in the APP/PS1 mice, mouse model of AD( Ou et al, 2018 ; Chen et al, 2021 ). Metformin also restored spine density, surface AMPA subunit GluA1 trafficking, LTP expression and spatial memory in the APP/PS1 mouse by inhibiting cyclin-dependent kinase 5 hyper-activation and cyclin-dependent kinase 5-dependent tau hyperactivation( Wang et al, 2020 ).…”
Section: Repurposing Of Anti-diabetic Agents As a Potential Treatment Targeting Cognitive Function In Ad And Schizophreniamentioning
confidence: 99%
“…Metformin protected rats against from methamphetamine-induced neurodegeneration via the modulation of Akt/GSK3 or CREB/BDNF signaling pathway, and the amelioration of behavioral changes such as anxiety, depression and cognitive deficits( Keshavarzi et al, 2019 ). Metformin attenuated spatial memory deficits, neuron loss in the hippocampus, decreased Aβ plaque load and chronic inflammation in the hippocampus and cortex, and enhanced neurogenesis in the APP/PS1 mice, mouse model of AD( Ou et al, 2018 ; Chen et al, 2021 ). Metformin also restored spine density, surface AMPA subunit GluA1 trafficking, LTP expression and spatial memory in the APP/PS1 mouse by inhibiting cyclin-dependent kinase 5 hyper-activation and cyclin-dependent kinase 5-dependent tau hyperactivation( Wang et al, 2020 ).…”
Section: Repurposing Of Anti-diabetic Agents As a Potential Treatment Targeting Cognitive Function In Ad And Schizophreniamentioning
confidence: 99%
“…Accumulation of Aβ increases the proinflammatory factors IL-1β and IL-6 levels in APP/PS1 mice [76]. It has been reported that metformin decreases the levels of IL-1β and IL-6 in APP/PS1 mice [76]. In addition, different studies have highlighted the anti-inflammatory and antioxidant function of metformin, with several pathways playing a key role in the activation of AMPK [147][148][149][150][151][152].…”
Section: Metformin Effects On Neuroinflammationmentioning
confidence: 99%
“…For the purpose of designing therapeutics or disease modifying agents for AD treatment, a wide variety of animal models have been developed to replicate the human environment of the disease [ 70 , 71 , 72 , 73 , 74 ]. In particular, the first aim of most AD animal models is to develop the neuropathological features that precede the cognitive dysfunction [ 75 , 76 , 77 ].…”
Section: Metformin As An Antidiabetic Drug Strategy For Alzheimer’s Disease Treatmentmentioning
confidence: 99%
See 2 more Smart Citations